THE SIGNIFICANCE OF THE ANOMALIES OF THE STYLOID PROCESS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Anomalies of the styloid process of the temporal bone are an important anatomical and clinical problem associated with various symptom complexes, including Eagle syndrome. This review systematizes data from studies published in 2010-2014 and indexed in the Scopus database, as well as a number of modern Russian publications on morphometry, clinical manifestations and diagnosis of this pathology. The review covers morphological variations, imaging techniques, epidemiological data, diagnostic and therapeutic features, which allows an in-depth presentation of this problem in a multidisciplinary context. a problem in a multidisciplinary context.